Links across ecological scales: Plant biomass responses to elevated CO2. (7th September 2022) - Maschler, Julia; Bialic‐Murphy, Lalasia; Wan, Joe; Andresen, Louise C.; Zohner, Constantin M.; Reich, Peter B.; Lüscher, Andreas; Schneider, Manuel K.; Müller, Christoph; Moser, Gerald; Dukes, Jeffrey S.; Schmidt, Inger Kappel; et al.
Abstract: The degree to which elevated CO2 concentrations (e[CO2 ]) increase the amount of carbon (C) assimilated by vegetation plays a key role in climate change. However, due to the short‐term nature of CO2 enrichment experiments and the lack of reconciliation between different ecological scales, the effect of e[CO2 ] on plant biomass stocks remains a major uncertainty in future climate projections. Here, we review the effect of e[CO2 ] on plant biomass across multiple levels of ecological organization, scaling from physiological responses to changes in population‐, community‐, ecosystem‐, and global‐scale dynamics. We find that evidence for a sustained biomass response to e[CO2 ] varies across ecological scales, leading to diverging conclusions about the responses of individuals, populations, communities, and ecosystems. While the distinct focus of every scale reveals new mechanisms driving biomass accumulation under e[CO2 ], none of them provides a full picture of all relevant processes. For example, while physiological evidence suggests a possible long‐term basis for increased biomass accumulation under e[CO2 ] through sustained photosynthetic stimulation, population‐scale evidence indicates that a possible e[CO2 ]‐induced increase in mortality rates might potentially outweigh the effect of increases in plant growth rates on biomass levels. Evidence at the global scale may indicate that e[CO2 ] has contributed to increased biomass cover over recent decades, but due to the difficulty to disentangle the effect of e[CO2 ] from a variety of climatic and land‐use‐related drivers of plant biomass stocks, it remains unclear whether nutrient limitations or other ecological mechanisms operating at finer scales will dampen the e[CO2 ] effect over time. By exploring these discrepancies, we identify key research gaps in our understanding of the effect of e[CO2 ] on plant biomass and highlight the need to integrate knowledge across scales of ecological organization so that large‐scale modeling can represent the finer‐scale mechanisms needed to constrain our understanding of future terrestrial C storage. Abstract : The degree to which elevated CO₂ concentrations (e[CO₂]) increase the amount of carbon assimilated by vegetation plays a key role in climate change. Yet, it remains highly uncertain. Here, we review the effect of e[CO₂] on plant biomass across multiple levels of ecological organization, scaling from physiological responses to population‐, community‐, ecosystem‐, and global‐scale dynamics. We find that evidence for a sustained biomass response to e[CO₂] varies across ecological scales. By exploring these discrepancies, we identify gaps in our understanding of the effect of e[CO₂] on plant biomass and highlight the need to integrate knowledge across scales of ecological organization.